LENGTH AND WIDTH RATIO EFFECT TO QUAIL PRODUCTIVITY (Coturnix coturnix japonica) IN PRODUCTION PERIOD - Destia, Miya; Sudrajat, Deden; Dihansih, Elis (Jurnal Peternakan Nusantara, 2017)
Quail has well known to many people. Quail is a land birds that has small body, short legs, and could not fly high. Quail has a plenty big potential as layer bird. This study aims to determine the optimal length and width ratio of the cage to obtain maximum quail (coturnix coturnix japonica) productivity. This study was conducted for one month to assess the effect of many treatments : P1 ratio of length and width cage 1 : 1 (length70 cm width 68 cm), P2 ratio of length and width cage 1,5 : 1 (length 84 cm width 57 cm), and P3 ratio of length and width cage 2 : 1 (length 98 cm width 49 cm). The following treatments performed on Quail with age around 7th to 11th weeks. Observed variables are feed consumption ratio, eggs productions, feed convention ration, quail day production, and the amount of weight eggs. Treatment with the ratio of length and width cage 2 : 1 with cage length 98 cm and width 49 cm affected the quail productivity such as feed consumption, average of eggs weight, feed conversion, quail day production, and amount of egg weight. Such treathments may increase the productivity of the quail of the production period.Keywords : quail, ratio, cage size, productivity, production period.